Sharp bound for the second Hankel determinant for a q-starlike function associated with the q-exponential function - Kumar, Karri Sanjay (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We determine the sharp bound of the second-order Hankel determinant H_2,2(f) and the coefficient functional for functions from the class of q-starlike functions S^*(L,q) by refining the results obtained in [Srivastava et al., Upper bound of the third Hankel determinant for a subclass of q-starlike functions associated with the q-exponential function, Bull. Sci. Math., 167 (2021); https://doi.org/10.1016/j.bulsci.2020.102942]. Moreover, we obtain sharp estimates for the Fekete–Szegö functional and the coefficient differences for the analyzed class of functions.